Ethics and whistle blowing : an investigation of the moral justification and framework for the practice of whistle blowing - Mafela, Muvhulawa Simon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2002.